PATHOLOGY OF THORACIC AORTA IN CONNECTIVE TISSUE DYSPLASIAS - G. I. Nechaeva; E. V. Semenova; A. A. Semenkin; I. V. Druk; V. P. Konev; O. I. Chindareva; L. А. Zhivilova; E. N. Loginova; T. V. Tkachenko (Российский кардиологический журнал)
The article is focused on a variety of aspects of aortic pathology in connective tissue dysplasias; approaches discussed to diagnostics and management of aortic dilation in dysplasias.